Is All Lost or A Lot Is Still Recoverable? A Case of 21st Century Indian Military Organizational Culture - TREHAN, DEVIKA; SONI, SWATI (The journal of contemporary issues in business and government, 2021)
The armed forces of a nation ought to be infallible organizations, scrupulous in action and deeds. They stand testimony to a nation’s strength and solidarity. Non-military organizations strive hard to achieve military like austerity, discipline, work ethos and credos. Today, Indian Armed Forces in general and Indian Army in particular is an organization with troubled culture, much of which is attributable to its resistance to change and strong stereotypes. While the socio-economic and technological changes have swept the world, the Indian Armed Forces have not been to appreciate and accommodate the changes that have impacted the very fabric of the organization. The authors have attempted to study the organization culture at the Indian armed forces through the lens of Warrick’s 2016 framework for high performance and low performance cultures. Adopting the mixed-method approach for data collection, the authors divided the study in two phases. In Phase I an in-depth systematic literature review was conducted and in phase II the authors conducted in-depth semi-structured interviews. The methodology was selected to be able to go into a lot of depth, and allow the participants to bring to fore the topics that the researchers had not even considered and to identify all empirical evidence to answer all the research question that were created using the Warrick’s 2016 framework. Citing replete evidences, the authors propose that the armed forces present a case of stagnating culture. Is all lost or a lot is still recoverable? is the idea with which the authors explored the extant literature and garnered evidence from world class armies across the globe. Drawing from the experiences of world class armies, the authors present a well-researched way forward for the Indian armed forces. The study is original in its intent and execution and presents insightful recommendations for all levels of leaders in the Indian armed forces, policy makers, bureaucrats and diplomats.